Vývoj High-tech polymerních hmot pro bezvýkopovou sanaci kanalizačních řádů - Hudec Jakubíková, Karolína (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Tato práce se zabývá vývojem high-tech polymerních hmot pro sanaci inženýrských sítí metodou bezvýkopové technologie (CIPP). Jedná se o plněnou speciální polymerní pryskyřici, kterou se sytí vhodná textilie (výstelka) ve formě rukávců, ty jsou následně vtahovány a polymerizovány přímo v sanovaném potrubí. V této práci byly vyvinuty nové hmoty s využitím druhotných surovin ve formě plniv v polymerní matrici s cílem zlepšení mechanických vlastností, včetně snížení finanční náročnosti těchto sanačních hmot. Použití druhotných plniv je v této práci ověřováno pomocí fyzikálně-mechanických zkoušek i z hlediska chemické odolnosti. Dále je zohledňovaná samotná zpracovatelnost dané receptury.

This thesis deals with the development of high-tech polymer materials for the rehabilitation of utility networks using the trenchless technology (CIPP) method. It is a filled special polymer resin, which saturates a suitable fabric (lining) in the form of sleeves, which are then drawn in and polymerized directly in the rehabilitated pipeline. In this work, new materials were developed using secondary raw materials in the form of fillers in the polymer matrix in order to improve the mechanical properties, including reducing the financial demands of these remediation materials. The use of secondary fillers in this work is verified by means of physical-physical-mechanical tests and chemical resistance. Furthermore, the processability of the newly designed recipes are taken into account.
Development of High-tech polymer materials for trenchless rehabilitation of sewer systems
Keywords: Metoda CIPP; sanace kanalizačních řádů; druhotné suroviny; sanace; polymerní pryskyřice; mechanická odolnost; chemická odolnost.; CIPP method; rehabilitation of sewages; secondary raw materials; rehabilitation; polymer resin; mechanical resistance; chemical resistence.